De Plagas Agrícolas en Trampa de Luz y Observaciones a Campo Del 24 de febrero al 1 de marzo de 2024 - Centeno, Alejandro René; Gasparetti, Graciela; Morano, Gonzalo Hector (AER San Francisco, INTA, 2025)
De Plagas Agrícolas en Trampa de Luz y Observaciones a Campo Del 24 de febrero al 1 de marzo de 2024